A complex between the Zika virion and the Fab of a broadly cross-reactive neutralizing monoclonal antibody revealed by cryo-EM and single particle analysis at 4.1 Å resolution - Tyagi, A. (Academic Press Inc., 2021)
10.1016/j.yjsbx.2020.100028